The Study of Kinetics and Isotherms of Methylene Blue Adsorption onto Activated Carbon-Loaded Cellulose Composite Bead - P. Sarkar (Journal of Scientific Research, 2023)
A novel adsorbent-activated carbon-loaded cellulose composite bead (AC-CCB) was synthesized by sol-gel conversion for the removal of methylene blue (MB) from an aqueous solution. The adsorbent was characterized by Fourier transform-infrared spectroscopy (FT-IR), field emission scanning electron microscope (FESEM), and X-ray energy dispersive spectroscopy (EDAX). The maximum dye removal was found to be 96.5, 92.3, and 81.8 %, corresponding to MB concentrations of 25, 50, and 100 mgL-1, respectively. Isotherm and the kinetic study were carried out with an AC-CCB dose of 1.0 g L-1, a shaking speed of 125 rpm, and the initial MB concentration ranging from 25-100 mg L-1. In order to study the kinetics of MB adsorption onto AC-CCB, the temperature was fixed at 298 K, whereas, for the isotherm study, the temperature varied from 298 to 318 K. The process followed pseudo-second-order kinetics with rate constant (k2) 28.7x10-2, 11.1x10-2 and 9.41x10-2 g.mg.min-1 corresponding to MB concentration of 25, 50 and 100 mg L-1. Freundlich, Langmuir, and Sips models were found to fit well with the adsorption data. The negative values and the positive values suggested that the adsorption of MB onto AC-CCB was spontaneous and endothermic.